A Maqasid Shariah Review of the Contra Legem Judge's Decision in the Application of Article 97 of the Compilation of Islamic Law - Baiq Tiffani Yunita; Djumikasih Djumikasih; Nur Chanifah (CV. AFDIFAL MAJU BERKAH, 2025)
The dynamics of the application of Article 97 of the Compilation of Islamic Law in the distribution of joint property after divorce shows the phenomenon of contra legem carried out by judges to achieve substantive justice. This study analyzes the philosophical construction of Article 97 of the Compilation of Islamic Law and the judge's decision that deviates from the provisions of the 50:50 division through the perspective of Maqasid Shariah. The research method uses normative juridical with a qualitative approach, analyzing the Supreme Court Decision Number 266K/AG/2010 and the Decision of the Jakarta High Court of Religion Number 126/Pdt.G/2013/PTA. JK as primary data. The results showed that judges applied distributive justice by taking into account the factual contributions of each party, resulting in a proportional division of 75:25 and 67:33 that deviated from the normative provisions. The findings reveal that the approach of Maqasid Syariah through the principles of hifdz al-mal and hifdz al-nafs provides theological legitimacy for deviations for the sake of substantive justice. The research concludes the need for a reformulation of Article 97 of the KHI by integrating the principle of proportionality of contribution to create a legal framework that is more adaptive to contemporary social realities without sacrificing legal certainty.